The standard for organizational project management (OPM). (Project Management Institute, 2018)
"The Standard for Organizational Project Management - First Edition provides a framework and integrated approach using portfolio, program, and project management to deliver organizational strategy for better performance, better results, and a sustainable competitive advantage. This standard is one of PMI's foundational standards and it is aligned with A Guide to the Project Management Body of Knowledge (PMBOK.